A Sistem Rekomendasi Pemilihan Lensa Kacamata Menggunakan Metode Weighting Product (WP) Pada Toko Optik Berkah - Ari Haryanto; Harry Witriyono (Jurnal Media Infotama, 2022)
Toko Optik Berkah is an optical shop that sells a variety of glasses and eyeglass lenses. In the process of selling their products, Blessing Optics Stores often have difficulty choosing lenses that suit the needs and desires of consumers, because of the large variety of types, materials, brands and prices of these lenses. This makes consumers only depend on the selection chosen by the Blessing Optics Shop. This also results in the length of time it takes for sellers to match consumer desires. The right solution to solve this problem is to create a recommendation system using the method of a decision support system, in this study the system to be used serves to facilitate consumers in purchasing eyeglass lenses. In this study, the Weigthing Product (WP) method was used. The use of the WP method is deemed appropriate to be used in this study. This method is useful for determining which lenses have the best quality, brand, type and price of the others. Seeing these problems, making the author to submit this research as a final project to create a recommendation system for choosing eyeglass lens products at the Blessing Optics Shop using the Weighted Product Method so as to solve these problems.